Biogenesis and Function of miRNAs and Their Role in Cancer - Yustina Nuke Ardiyan; Johana Puspasari Dwi Pratiwi (Jurnal Impresi Indonesia, 2024)
MicroRNA (miRNA) is a small RNA molecule that regulates post-transcriptional gene expression. miRNA combines with the RNA-induced silencing complex (RISC) and carries out its function in controlling translation. The formation of miRNA involves enzymes and proteins that cut it in its processing as well as protein complexes in the cytoplasm that make the miRNA mature. Several changes, for example deletion or overexpression, can occur in miRNAs, causing cancer growth. The aim of this study was to investigate the process of miRNA biogenesis as well as analyze how changes in miRNA expression can affect the biological pathways involved in cancer. This type of research is a literature review. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results show that the role of miRNAs is in the post-transcriptional regulation of genes. MiRNAs associate with the RISC complex and interact with mRNA through complementary base pairing thereby halting translation and promoting mRNA degradation. MiRNAs are deregulated in cancer, including over-expression of oncogenic miRNAs or deletion of miRNA characteristics as tumor inhibitors. The results of this research also provide a foundation for further education and advanced research in the field of molecular biology, particularly in genetic regulation and disease mechanisms.